Exploring Student Persistence in STEM Programs: A Motivational Model - Simon, Rebecca A.; Aulls, Mark W.; Dedic, Helena; Hubbard, Kyle; Hall, Nathan (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
To address continually decreasing enrollment and rising attrition in post-secondary STEM degree (science, technology, engineering, and mathematics) programs, particularly for women, the present study examines the utility of motivation and emotion variables to account for persistence and achievement in science in male and female students transitioning from high school to junior college. Consistent with self-determination theory (Deci & Ryan, 2012) and achievement-goal theory (Senko, Hulleman, & Harackiewicz, 2011), structural equation modelling based on data from 1,309 students from four English-language CEGEPs showed students’ achievement goals, self-efficacy, and perceived autonomy support to impact intrinsic motivation, emotions, and achievement that, in turn, predicted persistence in the science domain.